Development Of Teaching Materials Using Interactive Multimedia Computer Based Learning - Awal Rifqi Al Amri (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2016)
One of the factors that cause lower student learnrs is the elusiveness of materials teaching. Therefore, there should be arrange to development of materials teaching which are appropriate of the learners. The efforts of developing materials teaching by using interactive multimedia Computer Based leraning (CBL). This study aims to produce teaching materials math on the Subjects of circles valid criteria or feasible to use in the learning of mathematics. Teaching materials developed is the use of interactive multimedia teaching material Computer Based Learning (CBL) with Microsoft Power Point 2016 software, Quiz Qreator, and Flash. The method used is a method of research and development. The procedure of this study is parsimony steps ADDIE and Sugiyono is the analysis of potential and problems, data collection, product design, design validation, design revisions, product testing, product revision, evaluation, and conclusions. The results showed that the use of interactive multimedia teaching materials CBL has good views of the quality criteria for the validity and effectiveness. Based on the validation of the overall material experts gained 90.9% and is at a very decent criteria. While the results of the validation of the overall media experts gained 95% and is at a very decent criteria. Based on students' test results show that the student has completed the classical which reached 86.6% with an average value of 80.7. Then the results of the students' responses stated that 77.2% of mathematics teaching materials using interactive multimedia CBL good and fit for use in learning.